2020
DOI: 10.32731/smq.293.092020.06
|View full text |Cite
|
Sign up to set email alerts
|

The Dark Side of Spectator Behavior: Effects of Spectator Dysfunctional Behavior on Anger, Rumination, and Revisit Intention

Abstract: The purpose of this study is to examine the negative effects of spectator dysfunctional behavior (SDB) on other spectators' anger, rumination, and revisit intention. More specifically, in Study 1, we show that SDB (vs. spectator normal behavior [SNB]) elicited other spectators' anger and reduced revisit intention. Anger significantly mediated the relationship between SDB (vs. SNB) and revisit intention. The negative effects of SDB and anger on revisit intention became positive as team identification increased.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 29 publications
(72 reference statements)
0
12
0
Order By: Relevance
“…For example, Kim et al (2020a) found a high severity SDB (vs. a low severity SDB) reduced witnesses' revisit intention. Similarly, Kim and Byon (2020) found that SDB increased other spectators' anger and evoked rumination after the event, which negatively affected revisit intention.…”
Section: Theoretical Backgroundmentioning
confidence: 88%
See 4 more Smart Citations
“…For example, Kim et al (2020a) found a high severity SDB (vs. a low severity SDB) reduced witnesses' revisit intention. Similarly, Kim and Byon (2020) found that SDB increased other spectators' anger and evoked rumination after the event, which negatively affected revisit intention.…”
Section: Theoretical Backgroundmentioning
confidence: 88%
“…The more spectators feel connected to their favorite team, the more likely they are to act in a way categorized as SDB (Larkin and Fink, 2019). Research of SDB in consumer behavior has been extended to account for spectators' emotional, psychological and behavioral responses to SDB (Kim and Byon, 2020; Kim et al , 2020a).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations